After Liberal Peace: The Changing Concept of Peace-building - Richmond, Oliver P (2016)
It has become increasingly apparent that both the liberal peacebuilding framework of the 1990s (as defined by the UN’s Agenda for Peace), and the more critical responses since (as outlined in the recent High Level Panel Report on UN Peace Operations), have been surpassed by current events and new dynamics.